2002
DOI: 10.3168/jds.s0022-0302(02)74182-9
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Milk Fatty Acid Profiles Produced by Feeding DietsContaining Solin, Flax and Canola

Abstract: Fatty acid profiles with emphasis on linoleic, linolenic, oleic, and conjugated linoleic acid (CLA) were compared in milk from dairy cows fed diets containing 3.25% supplemental fat and a control diet containing no supplemented fat. The fat was supplied by either whole ground solin, flax, or canola oilseed. Solin (linola) is a new cultivar of flax that contains 28% linoleic acid in the seed, Twelve multiparous Holstein cows were assigned to one of four dietary treatments. The experimental design was a 4 x 4 La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
61
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 18 publications
26
61
3
1
Order By: Relevance
“…The increased milk yield of supplemented cows (Table 4) agrees with the majority of studies in the literature (Scott et al, 1995;Petit et al, 2004;Dirandeh et al, 2013), although some authors report that the supplementation with fatty acids does not affect milk production (Ward et al, 2002;Gonthier et al, 2005). Petit et al (2004) suggest that a greater fat mobilization contributes for a greater milk yield in cows supplemented with fatty acids.…”
Section: Resultssupporting
confidence: 84%
“…The increased milk yield of supplemented cows (Table 4) agrees with the majority of studies in the literature (Scott et al, 1995;Petit et al, 2004;Dirandeh et al, 2013), although some authors report that the supplementation with fatty acids does not affect milk production (Ward et al, 2002;Gonthier et al, 2005). Petit et al (2004) suggest that a greater fat mobilization contributes for a greater milk yield in cows supplemented with fatty acids.…”
Section: Resultssupporting
confidence: 84%
“…However, fat supplementation at 2% of dietary DM resulted in an average 11.7% increase in milk fat yield compared with that of the control treatment. Some researchers (Bell et al, 2006) reported that fat supplementation resulted in a decrease in milk fat content while others reported no effect (Ward et al, 2002;Bu et al, 2007). The reduction of milk fat content may be due to the fact that too much unsaturated FA destroy the membrane of bacteria and further decrease the fibre digestion, which may cause decreased acetate production (Onetti et al, 2001;Ye et al, 2009).…”
Section: Feed Intake Milk Yield and Milk Compositionmentioning
confidence: 99%
“…However, the same group [14] showed that in vitro 18:2n-6 inhibited stimulated PGF2α production by maternal endometrial cells as did a mixture of conjugated linoleic acids (CLA). Ward et al [15] showed that a diet supplemented with 18:2n-6 was more effective in increasing CLA than a diet supplemented with 18:3n-3, possibly because extra steps are required to produce CLA from 18:3n-3 compared to 18:2n-6 [16]. Therefore, the synthesis of series 2 PG could be affected in several ways.…”
Section: Introductionmentioning
confidence: 99%